Strategi Pengembangan UMKM Berbasis Pengetahuan Khas Perempuan Melalui Konsep Micro-Franchise di Kota Kendari - Diamond Limbong; Astriwati; Ayuningtyas Putri Mumpuni; Ami Nurhayati; Yuni Maimuna (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to analyze the effect of women’s distinctive knowledge on the development of Micro, Small, and Medium Enterprises (MSMEs), with the micro-franchise concept serving as a mediating variable in Kendari City. The research employs a quantitative approach using a survey method. The population consists of women-owned MSMEs in Kendari City, with a sample of 32 respondents selected through purposive sampling based on criteria that the MSMEs utilize local knowledge in their business activities. Data analysis techniques include validity and reliability testing, multiple linear regression analysis, and the Sobel test to examine the mediating role of the micro-franchise concept. The results indicate that women’s distinctive knowledge has a positive and significant effect on the adoption of the micro-franchise concept, but does not have a significant direct effect on MSME development. In contrast, the micro-franchise concept has a positive and significant effect and is able to mediate the relationship between women’s distinctive knowledge and MSME development. These findings suggest that women’s distinctive knowledge requires a structured business management mechanism in order to generate a tangible impact on the development strategies of women-owned MSMEs based on local potential